(untitled) (International Seven Journal of Health Research, 2023)
The UNEC-CASU Health Care Center is a school clinic for the Physiotherapy course at the Centro Universitário de Caratinga-UNEC Nanuque higher education institution. It was founded in 2010 and aims to provide practical classes for the Physiotherapy course, as well as the compulsory supervised internship, which takes place from the eighth period of the course. Objective: To verify, through a documentary analysis, information on the epidemiological profile of patients at a physiotherapy school clinic located in the city of Nanuque-MG. Methodology: By means of an exploratory documentary study, this study analyzed the characteristics of the epidemiological profile, as well as the pathologies presented by the patients of a Physiotherapy school clinic, observing factors that interfere positively or negatively both in their health and in the quality of care, with a view to the results obtained through the Physiotherapy treatment carried out by trainees from a higher education institution in the city of Nanuque-MG. Results: It was observed that the population seeks physiotherapy rehabilitation services because they have a greater number of musculoskeletal injuries, portraying difficulties in carrying out everyday activities. Conclusion: It can be concluded that, in general, among the various areas of physiotherapy worked on in physiotherapy clinics, the specialty of orthopaedic and trauma physiotherapy is the most sought-after area in the municipality of Nanuque, Minas Gerais, and that the population seeks physiotherapy rehabilitation services because they have a greater number of musculoskeletal injuries, including difficulties in carrying out their daily tasks.